Tagang System at Pedid River - Eva Kristin, Larry Sait; Wong, Swee Kiong; Neilson Ilan, Mersat (UNIMAS Publisher, 2023)
This book chapter discusses about Tagang System implemented at Pedid River which is one of the important findings recorded from the multidisciplinary expedition to Bungo Range in December 2017.